2020
DOI: 10.5488/cmp.23.23608
|View full text |Cite
|
Sign up to set email alerts
|

Magnetorheological effect in elastomers containing uniaxial ferromagnetic particles

Abstract: The description of the collective magnetorheological effect induced by magnetic field in magnetoactive elastomers is proposed. The condition of consistency is used between magnetic and mechanic momenta of forces exerted on magnetically uniaxial ferromagnetic particles in elastomer at their magnetization. The study shows that even in the case of small concentration of particles, the value of magnetically-induced shear can be anomalously large, reaching up to tens of percent. The deformation of magnetoactive ela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In [66], it was shown that the critical rotation of a spherical magneto-anisotropic particle in an elastomer matrix induced by the magnetic field can provoke a magnetic phase transition in the particle, which is an orientational transition [67] induced by a magnetic field. As a result, the rotation of the particles can affect the MAE magnetoelasticity and lead to an anomalous field behavior of shear deformation in the MAE [68].…”
Section: Introductionmentioning
confidence: 99%
“…In [66], it was shown that the critical rotation of a spherical magneto-anisotropic particle in an elastomer matrix induced by the magnetic field can provoke a magnetic phase transition in the particle, which is an orientational transition [67] induced by a magnetic field. As a result, the rotation of the particles can affect the MAE magnetoelasticity and lead to an anomalous field behavior of shear deformation in the MAE [68].…”
Section: Introductionmentioning
confidence: 99%